Interplay of overseas employment of Bangladesh and sustainable development goals :: an introspective analysis (Bangladesh Journal of Public Administration, 2021)
Bangladesh Government has taken various initiatives for sustainable economic growth, creating strong employment market and upholding people’s prosperity in line with the achievement of targets of Sustainable Development Goals (SDGs) by 2030. Hence, utilization of huge active workforce consisting of 64 percent of the total population is a major concern that appears because of small employment market and the necessity of socio-economic development of this huge group as well as country. Engaging these potential human resources in overseas employment (OE) market has become a mandatory solution for development.OE constitutes of 9 per cent of total active workforce who are currently working across the world. In addition, about 30 million people are dependent on them. It indicates that the contribution of this active group on the society and economy is enormous. The study analyses connection between OE and SDGs, contribution of OE in achieving SDGs for socio-economic development and confusion about the sustainability of development. This paper utilized qualitative methodology and analysis was done using interpretative approach. Both primary and secondary data were used. The study found that overseas employees send about 15 billion US dollars every year to keep the economic growth stable and sustain foreign reserve. The remittance sent by the expatriates to their families is primarily used for buying food & cloth, educating their children, building houses and sanitation, establishing small businesses, contributing to social and religious organizations and also for buying permanent property i.e. buying land and houses with the saved money. Although their spending pattern signifies unproductive sector, it considerably contributes in the overall development of Bangladesh. The intended and unintended benefits of OE are directly connected to almost all SDGs. It is argued that without the contribution of OE, achievement of SDGs is unthinkable. Confusion of achieving sustainability arises as expatriates face myriad challenges because of extra cost, hazardous procedures, middle men involvement at home and abroad, precarious working conditions, unstructured job, misbehavior of foreign employers, non-availability of database of expatriates. A meaningful number of expatriates die every year because of accidents or lack of workplace safety. As the huge number of active workforce are migrant workers, country lacks of young generation and face social crisis. Receiving countries also face numerous challenges e.g. unemployment, overflow of illegal migrant workers, socio-economic and political crisis. These problems seriously affect expatriate workers who face banning and restriction. The study suggests to create opportunity in internal employment market to utilize potential human resources, develop and send skilled workforce to abroad, design real time database for all migrants, practice weekly monitoring for women and risky job holders, and develop effective negotiation with the host countries. Overseas employment, SDGs, economic growth, workplace safety, internal employment market, real-time data base